Equipment design for biosorption studies with microorganisms - Jensen, Thomas E.; Crang, Mary C.; Crang, Richard F.E. (Electronic Journal of Biotechnology, 2008)
Two laboratory devices have been designed for experimental use in biosorption studies involving the uptake and controlled release of elements from encapsulated living cells of microorganisms. The first device is an alginate bead maker capable of producing uniform (1.5 mm diameter) sodium alginate beads with encapsulated microorganisms. The second device is a flow-cell that can subject the encapsulated microorganisms to changing fluids, streaming gaseous microaerophyllic conditions, and which also allows for samples of fluid and beads to be extracted at any time during changing experimental conditions. Both devices are novel and simple in their design, and enable improved accuracy and precise handling of encapsulated specimens with minimal labour and expenditure.